Polymorphisms in the 3′UTR Region of ESR2 and CYP19A1 Genes in Women With Endometriosis. (July 2020) - Szaflik, Tomasz; Smolarz, Beata; Romanowicz, Hanna; Bryś, Magdalena; Forma, Ewa; Szyłło, Krzysztof
Abstract: Objective: ESR2 and CYP19A1 genes play a major role in the hormonal control of women with endometriosis. The aim of the study was to analyze single nucleotide polymorphisms (SNPs) in the 3'UTR region of ESR2 and CYP19A1 genes. The study aimed at localisation of new polymorphisms, the nucleotide variants of which determine the level of susceptibility to endometriosis. Study design: The study included n = 200 patients: 100 with endometriosis and 100 healthy controls. The Sanger's sequencing method was applied for polymorphism analysis. Results: Statistically significant correlations were identified between new, not previously described, two SNPs of ESR2 gene and endometriosis: rs4986938 (G>A) and rs928554 (A>G). In the case of rs4986938 polymorphism, the genotype AA was found to decrease the risk of endometriosis (OR = 0.24 95 % PU 0.05-1.22, p = 0.04). Analysis of the rs928554 polymorphism revealed that the occurrence of the AG genotype reduced the risk of endometriosis (OR = 0.38 95 % PU 0.21-0.71, p = 0.002). There were no differences in the distribution of genotypes of the polymorphisms rs10046 (C>T) and rs4646 (C>A) of CYP19A1 gene between patients and control. Conclusions: Further studies are necessary in groups with higher numbers of patients to explain whether the above-mentioned polymorphisms may be the risk factors for endometriosis. Highlights: TThe results indicate that polymorphisms of ESR2 gene may be associated with the incidence of endometriosis. It was demonstrated that rs4986938 and rs928554 polymorphisms of ESR2 gene may be a risk factor for endometriosis. The polymorphisms of ESR2 gene may be associated with the incidence of endometriosis observed in Poland.